If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3t + -1) = y Reorder the terms: 2(-1 + 3t) = y (-1 * 2 + 3t * 2) = y (-2 + 6t) = y Solving -2 + 6t = y Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6t = 2 + y Combine like terms: -2 + 2 = 0 0 + 6t = 2 + y 6t = 2 + y Divide each side by '6'. t = 0.3333333333 + 0.1666666667y Simplifying t = 0.3333333333 + 0.1666666667y
| S=15T+180 | | 2x+-4=1 | | 8x^2+4=44 | | 12x-8=x+25 | | F(1.5)=[x]+1 | | 10x-7=3x+7 | | 7x^2+57x+42=7+3x | | 6-24x+14+35x=53 | | 10X^2-2X+8=0 | | 7x^2+57x+42=7 | | 6x-3x=15+4x | | 5x-1+3x=9 | | 6/7x2/5 | | a^2-13a=-12-6a | | 6a^2-13a+6a=-12 | | 2x+5-3x+1=0 | | 3/8*10x | | 4log(4x+5)=-2 | | 5x-1-3=2 | | 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 |